2020
DOI: 10.3233/wor-203250
|View full text |Cite
|
Sign up to set email alerts
|

A ‘new normal’ following COVID-19 and the economic crisis: Using systems thinking to identify challenges and opportunities in disability, telework, and rehabilitation

Abstract: BACKGROUND: The novel coronavirus (COVID-19) that emerged in late 2019, and later become a global pandemic, has unleashed an almost unprecedented global public health and economic crisis. OBJECTIVE: In this perspective, we examine the effects of COVID-19 and identify a likely ‘new normal’ in terms of challenges and opportunities within the fields of disability, telework, and rehabilitation. METHODS: We use a systems thinking lens informed by recent empirical evidence and peer-reviewed qualitative accounts rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 74 publications
(98 reference statements)
1
57
0
4
Order By: Relevance
“…During the first wave of the COVID-19 pandemic, many healthcare services (e.g., outpatient, day services, some in-patient rehabilitation services, assistive devices programs), essential for people with disabilities (e.g., to maintain or recover health and function, manage chronic conditions, prevent secondary conditions, benefit from psychosocial support), were either shutdown or operating at a reduced capacity due to lockdown restrictions. In other words, if they were open, they were operating without sufficient human resources, beds, or other healthcare resources that were diverted to fighting the pandemic [9,14,48,71,80,84,107].…”
Section: Disrupted Access To Healthcare (Other Than For Covid-19)mentioning
confidence: 99%
See 2 more Smart Citations
“…During the first wave of the COVID-19 pandemic, many healthcare services (e.g., outpatient, day services, some in-patient rehabilitation services, assistive devices programs), essential for people with disabilities (e.g., to maintain or recover health and function, manage chronic conditions, prevent secondary conditions, benefit from psychosocial support), were either shutdown or operating at a reduced capacity due to lockdown restrictions. In other words, if they were open, they were operating without sufficient human resources, beds, or other healthcare resources that were diverted to fighting the pandemic [9,14,48,71,80,84,107].…”
Section: Disrupted Access To Healthcare (Other Than For Covid-19)mentioning
confidence: 99%
“…Any reduction in physical inactivity or person-level deconditioning can lead to novel disability risks and exacerbate existing ones [80,84,101]. Especially in older individuals with neurocognitive disorders or other impairments, a forced reduction of motor/physical activity can cause a progressive loss of personal and instrumental autonomy, as well as a possible worsening of other aging-related clinical concerns, such as sarcopenia, with a subsequent increased risk of falls and other complications [78,84,108].…”
Section: Reduced Physical Activity Leading To Health and Functional Declinementioning
confidence: 99%
See 1 more Smart Citation
“…In residential care settings, shielding and self-isolation were difficult during the first wave of the pandemic. This was due to the: initial unpreparedness of the facilities at the pandemic outset, shared use of essential living spaces, crowding and shared rooms, proximity to other residents, residents’ difficulty understanding new rules imposed suddenly, difficulty in maintaining standards of hygiene during home visits, multiple shift staffing patterns, staff working in multiple settings, and high levels of personal care assistance required from staff (e.g., with eating, toileting, or transferring from bed to wheelchair) [ 16 , 30 , 31 , 36 , 38 , 39 , 43 , 51 , 53 , 54 , 59 , 70 , 78 ]. Indeed, stemming from the latter reason, many articles pointed out that a wide range of people with disabilities who rely on assistants for basic activities of daily living have greater risks of infection [ 6 , 32 , 36 , 41 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Globally, another analysis showed that pages of the World Health Organization’s website, March–May 2020, were only 60% compliant regarding web accessibility guidelines [ 75 ]. Additionally, people with sensory processing and visual impairments may need to rely or depend on touch and tactile senses for stimulus or to perform their routine activities or outdoor movement, and thereby face greater infection risks [ 33 , 38 , 40 , 43 , 49 ].…”
Section: Resultsmentioning
confidence: 99%